Associations between epidermal growth factor receptor mutations and histological subtypes of lung adenocarcinoma according to the IASLC/ATS/ERS classification in Chinese patients. Issue 6 (20th September 2017) - Wang, Tengteng; Zhang, Yi; Liu, Baodong; Hu, Mu; Zhou, Naikang; Zhi, Xiuyi
Abstract : Background: This retrospective study was conducted to investigate the relationship between epidermal growth factor receptor (EGFR) mutation and histological subtypes of lung adenocarcinoma according to the International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society (IASLC/ATS/ERS) classification in Chinese patients. Methods: Three hundred and seventy six surgically resected lung adenocarcinomas from Chinese PLA General Hospital were included in the study. Patients' clinical and pathological characteristics including age, gender, smoking history, tumor size, tumor node metastasis stage, and tumor differentiation were analyzed. Histologic subtypes of adenocarcinoma were categorized according to the IASLC/ATS/ERS classification of lung adenocarcinoma. An amplification‐refractory mutation system was performed to detect EGFR mutations. Results: One hundred and fifty three lung adenocarcinomas had EGFR mutations. In univariate analysis, EGFR mutations were associated with gender ( P < 0.001), smoking history ( P < 0.001), tumor differentiation ( P < 0.001), and acinar predominant ( P < 0.001), papillary predominant ( P = 0.034), solid predominant ( P = 0.022), invasive mucinous ( P = 0.012) and mucinous ( P = 0.001) subtypes. Conclusions: In Chinese patients with lung adenocarcinoma, smoking history, tumor differentiation, and acinar predominant and mucinous subtypes were independent predictors of EGFR mutation.